2020
DOI: 10.3390/pathogens9020073
|View full text |Cite
|
Sign up to set email alerts
|

New Approaches for Escherichia coli Genotyping

Abstract: Easy-to-perform, fast, and inexpensive methods of differentiation of Escherichia coli strains beyond the species level are highly required. Herein two new, original tools for genotyping of E. coli isolates are proposed. The first of the developed method, a PCR-RFLP (polymerase chain reaction-restriction fragment length polymorphism) test uses a highly variable fliC gene, encoding the H antigen as a molecular target. The designing of universal pair of primers and selection of the optimal restriction enzyme RsaI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…IPEC bacteria are associated with infections of the gastrointestinal tract. Several pathotypes can be distinguished among IPEC strains: enteropathogenic E. coli (EPEC), enterotoxigenic E. coli (ETEC), enterohaemorrhagic E. coli (EHEC), enteroinvasive E. coli (EIEC), enteroaggregative E. coli (EAEC), adherent invasive E. coli (AIEC), and diffusely adherent E. coli (DAEC) [ 96 ]. ExPEC strains cause infections in extraintestinal anatomic sites, and in this group include: uropathogenic E. coli (UPEC) associated with urinary tract infection in human and animals, neonatal meningitis-associated E. coli (NMEC), septicaemic E. coli (SePEC) causing systemic infection in human and animals, avian pathogenic E. coli (APEC) that cause avian colibacillosis, and a potentially emerging ExPEC lineage named endometrial pathogenic E. coli (EnPEC) [ 97 , 98 ].…”
Section: Mechanisms Of Transfer Of Resistance Based On Examples Of Va...mentioning
confidence: 99%
“…IPEC bacteria are associated with infections of the gastrointestinal tract. Several pathotypes can be distinguished among IPEC strains: enteropathogenic E. coli (EPEC), enterotoxigenic E. coli (ETEC), enterohaemorrhagic E. coli (EHEC), enteroinvasive E. coli (EIEC), enteroaggregative E. coli (EAEC), adherent invasive E. coli (AIEC), and diffusely adherent E. coli (DAEC) [ 96 ]. ExPEC strains cause infections in extraintestinal anatomic sites, and in this group include: uropathogenic E. coli (UPEC) associated with urinary tract infection in human and animals, neonatal meningitis-associated E. coli (NMEC), septicaemic E. coli (SePEC) causing systemic infection in human and animals, avian pathogenic E. coli (APEC) that cause avian colibacillosis, and a potentially emerging ExPEC lineage named endometrial pathogenic E. coli (EnPEC) [ 97 , 98 ].…”
Section: Mechanisms Of Transfer Of Resistance Based On Examples Of Va...mentioning
confidence: 99%
“…Intestinal pathogenic E. coli (IPEC) bacteria are associated with infections of the gastrointestinal tract, while extraintestinal pathogenic E. coli (ExPEC) strains cause infections in extraintestinal anatomic sites. Several pathotypes can be distinguished among IPEC strains: enterotoxigenic E. coli (ETEC), enteropathogenic E. coli (EPEC), enterohaemorrhagic E. coli (EHEC), enteroinvasive E. coli (EIEC), enteroaggregative E. coli (EAEC), adherent invasive E. coli (AIEC), and diffusely adherent E. coli (DAEC) [ 1 ]. ExPEC strains include avian pathogenic E. coli (APEC), uropathogenic E. coli (UPEC), neonatal meningitis E. coli (NMEC), and sepsis-associated E. coli (SEPEC) [ 1 , 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several pathotypes can be distinguished among IPEC strains: enterotoxigenic E. coli (ETEC), enteropathogenic E. coli (EPEC), enterohaemorrhagic E. coli (EHEC), enteroinvasive E. coli (EIEC), enteroaggregative E. coli (EAEC), adherent invasive E. coli (AIEC), and diffusely adherent E. coli (DAEC) [ 1 ]. ExPEC strains include avian pathogenic E. coli (APEC), uropathogenic E. coli (UPEC), neonatal meningitis E. coli (NMEC), and sepsis-associated E. coli (SEPEC) [ 1 , 2 ]. Characteristic virulence factors, which play a decisive role in pathogenesis, have been defined for each of these pathotypes [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previously, in silico enzymatic restriction studies have demonstrated the intraspecies genetic variability in other bacteria, such as identifying clusters and subclusters in the streptokinase gene of Streptococcus 26 , the identification of E. coli genotypes, which also suggested updating the existing classifications 30 . Its usefulness was also proven in constructing new classifications in the study species, with a highly reliable discrimination power, such as the one performed using the cpn60 gene of phytoplasmas 28 .…”
Section: Discussionmentioning
confidence: 99%